Multiple Eschars in Scrub Typhus - Mohan Kaushik, Rajeev (The Japanese Society of Tropical Medicine, 2014)
An eschar is highly suggestive of scrub typhus in a case of fever. Multiple eschars are rare in scrub typhus. We present a picture of multiple eschars in scrub typhus.